SCWR transient safety analysis code SCAC-CSR1000. (August 2015) - Liu, Liang; Zhou, Tao; Li, Yu; Chen, Juan; Ali, Muhammad Zeeshan; Xiao, Zejun
Abstract: CSR1000 was selected as the research object. A code named SCAC-CSR1000 has been developed based on the SCAC code. The reliability of the code was verified by comparing the result of SCAC-CSR1000 and SCTRAN. Then the safety analysis was carried out. Five events were selected, that are partial loss of reactor coolant flow, isolation of main steam line, uncontrolled CR withdrawal, reactor coolant pump seizure and loss of feed water heating. By the numerical analyses, it was found that the MCST does not exceed 1260 °C, meets the design safety requirements. The 2nd MCST are higher than 1st MCST. The isolation of main steam line has the least safety margin. Highlights: The transient safety analysis code for CSR1000 is introduced. The watt's correlation is used to get conservative results. The redistribution of mass flow rate in each channel is achieved by pressure drop balance calculation. The reactor coolant pump seizure accident will cause a backflow phenomenon.